The Black Mirror of the Pupil of the Eye: Around the Eye that Sees and Is Seen: Ibn al-ʿArabī, Bill Viola - Gonzalo Carbó, Antoni (Religions, 2023)
The present article traces the symbols of the eye (Greek: κόρη [maiden, concubine, pupil of the eye]; Latin: pūpilla; Hebrew: īshōn bath ʿāyin (‘apple of the eye’ or the ‘pupil of the eye’ [lit. ‘daughter of an eye’], i.e., the feminine divine Presence [Shĕkhīnāh]); Arabic: ʿayn; Persian: chashm) and the black pupil of the eye (Arabic: insān al-ʿayn; Persian: mardum-i chashm) in Sufism, both—in the context of Andalusian Sufism, specifically in Ibn al-ʿArabī’s poem entitled ‘I saw a Girl…’, in whose dark pupil or abyssal blackness (Arabic: ḥawar; Hebrew: īshōn), pleasure of the gaze (naẓar) and repository of the secret (sirr), resides the Beloved—as in the medieval Persian gnosis of the followers of al-Sahykh al-Akbar—Fakhr al-Dīn ʿIrāqī and Maḥmūd Shabistarī—, and the mystical poet Ḥāfiẓ Shīrāzī. Ibn al-ʿArabī and Shabistarī have had an explicit influence on the work of the reputed American video artist Bill Viola (Queens, New York, 1951), specifically in his two video/sound installations—He Weeps for You (1976) and I Do Not Know What It Is I Am Like (1986), in which the common image of the mirror pupil of the eye summarizes the entire ancient Neoplatonic conception of the θεωρία (contemplatio, speculatio).